THE EFFECTIVENESS OF HYPNOSIS IN OVERCOMING DENTAL ANXIETY - Anha Rizza Muzenin; Musri Amurwaningsih; Erna Dwi Agustin (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Hypnosis is a sleep-like state that causes a reduction in the conscious mind for the analysis process, and in this state, it is dominated by the subconscious mind so that it is easy to give suggestions. Hypnosis can be used to reduce and even eliminate anxiety by giving positive suggestions to the subconscious mind. Excessive anxiety experienced by patients can interfere with dental care and cause phobias. Several studies have shown that hypnosis is useful as an additional intervention to reduce anxiety in dental patients. However, until now there is still rarely a literature review that discusses this matter. Method: Literature Review by conducting a literature search using several databases, namely Google Scholar, PubMed, and NCBI. The literature used in this study was those that discusses the effectiveness of hypnosis in overcoming dental anxiety. Results: The results of the search for journal literature from the database above were screened and found as many as 82 journals, then the journals were reviewed again which met the inclusion criteria and those that entered the exclusion criteria. The total reference journals used in this literature review are 24 journals. Dental anxiety is a body response that is perceived as a threat or danger in a dental care situation. Dental anxiety can be treated with hypnosis. Conclusion: Stand-alone hypnosis, hypnosis with the addition of other non-pharmacological methods, or hypnosis with additional sedation showed effectiveness in overcoming anxiety.